2015
DOI: 10.4321/s0213-61632015000100002
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced hallucination: a case/non case study in the French Pharmacovigilance Database

Abstract: Background and Objectives: Hallucinations are sensory perceptions which occur without external stimuli. There are associated with psychiatric disease but also can be related to organic disease and drug or toxic exposure. The purpose of our study was to investigate the association between exposure to medications and the reporting of hallucinations using data from the spontaneous-reporting French Pharmacovigilance Database (FPVD). Methods: We used the case/noncase method in the FPVD. Cases were all the observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Dementia, delirium, tumor, epilepsy, serotonergic syndrome, Charles‐Bonnet syndrome, inappropriate release of antidiuretic hormone, hyponatremia, and drugs can cause hallucinations. Drug‐induced hallucinations are often visual, as in our patient 3,4 . Drugs reported to cause hallucinations include zolpidem, fluoroquinolones, valacyclovir, narcotic analgesics, levodopa, benzodiazepine, antidepressants, methylphenidate, proton pump inhibitors, voriconazole, and oxybutynin 3 .…”
Section: Discussionmentioning
confidence: 73%
“…Dementia, delirium, tumor, epilepsy, serotonergic syndrome, Charles‐Bonnet syndrome, inappropriate release of antidiuretic hormone, hyponatremia, and drugs can cause hallucinations. Drug‐induced hallucinations are often visual, as in our patient 3,4 . Drugs reported to cause hallucinations include zolpidem, fluoroquinolones, valacyclovir, narcotic analgesics, levodopa, benzodiazepine, antidepressants, methylphenidate, proton pump inhibitors, voriconazole, and oxybutynin 3 .…”
Section: Discussionmentioning
confidence: 73%
“…A study using the French Pharmacovigilance Database, which recorded 469,181 reports of adverse effects between 1985 and 2013, found that 482 patients reported hallucinations of the total 12,184 patients who had received opioids. 42 Although the duration of opioid therapy was not standardized, these data provide suggestion to the overall incidence of opioid-induced hallucinations. 42 Tramadol was involved most often with an incidence of 240, an odds ratio of 6.3, and 95% confidence interval of 5.5 to 7.2, whereas morphine was next with an incidence of 143, an odds ratio of 4.4, and 95% confidence interval of 3.7 to 5.2.…”
Section: Resultsmentioning
confidence: 99%
“…42 Although the duration of opioid therapy was not standardized, these data provide suggestion to the overall incidence of opioid-induced hallucinations. 42 Tramadol was involved most often with an incidence of 240, an odds ratio of 6.3, and 95% confidence interval of 5.5 to 7.2, whereas morphine was next with an incidence of 143, an odds ratio of 4.4, and 95% confidence interval of 3.7 to 5.2. The increased incidence associated with tramadol may occur because along with its opioid-agonist properties, it also inhibits reuptake of norepinephrine and serotonin.…”
Section: Resultsmentioning
confidence: 99%
“…However, following its extensive use for chronic pain relief and also in drug-abuse cases, dependency and, after long-term use, the occurrence of withdrawal symptoms were observed. Tramadol was associated with visual and auditory hallucinations, psychotic disorder, and confusional state, which might resemble the withdrawal symptoms of serotonin reuptake blockers rather than opioid blockers, and this may be related to tramadol's mechanism of action as a serotonin and epinephrine reuptake blocker [47,48]. Consistently, a report by the Adverse Drug Reactions Advisory Committee of Australia found that confusion, hallucinations, convulsions, and serotonin syndrome were the most serious adverse reactions recorded among all tramadol-related reports [49,50].…”
Section: Abuse and Diversion Issuesmentioning
confidence: 99%